The Service Sector as India's Road to Economic Growth? - Barry Eichengreen; Poonam Gupta (Indian Council for Research on International Economic Relations (ICRIER), 2010)
Among fast growing developing countries, India is distinctive for the role of the service sector. However, sceptics have raised doubts about both the quality and sustainability of the increase in service sector activity and its implications for economic development. Using National Accounts Statistics and cross-county data, we show that the growth of services has been broad-based. We show that the growth of service sector employment is not simply disguised manufacturing activity. We also find that the skilled-unskilled mix of labour in the two sectors is becoming increasingly similar. Hence, it is no longer obvious that manufacturing is the main destination for the vast majority of Indian labour moving into the modern sector and that modern services are only a viable destination for the highly skilled few. To the extent that the expansion of both modern manufacturing and modern services is constrained by the availability of skilled labour, this just underscores the importance for India of continuing to invest in labour skills. We conclude that sustaining economic growth and raising living standards will require shifting labour out of agriculture into both manufacturing and services and not just into one or the other.
Keywords: O10; O11; O14; 330; Services; structural change; India; employment; Dienstleistungssektor; Branchenentwicklung; Wirtschaftswachstum; Indien